A Brief Discussion on Historical Truth and Artistic Truth in the Creation of History Paintings - Li, Jiapei (International Journal of Social Sciences and Public Administration, 2025)
Historical painting creation stands as a significant intersection of art and history, valuing the reproduction of historical truth and the conveyance of historical spirit through artistic means. This paper delves into the historical and artistic truth in historical painting creation, arguing that historical truth forms the cornerstone while artistic truth embodies the personalized expression of artists. Moreover, both historical and artistic truth coexist in opposition and unity in historical painting creation, and their balance is crucial for producing exceptional works. By analyzing specific historical paintings, this paper proposes principles and practical methods for balancing historical and artistic truth, offering theoretical guidance and practical reference for historical painting creation.